Leiomyoma of the Round Ligament of the Uterus Mimicking Inguinal Hernia - Ioulia Maria Christodoulou; Argiris Angelopoulos; Petros Siaperas; Argyrios Ioannidis; Andreas Skarpas; Antreas Tellos; Georgios Velimezis; Ioannis Karanikas (Case Reports in Surgery)
Masses of the round ligament of the uterus are uncommon. Leiomyomas are the most common of them, followed by mesothelial cysts and in some cases endometriosis. The exact incidence is not known, but most cases are frequently encountered during the fertility age. Leiomyomas are benign tumors, which can present as hernias, lymph nodes, or other inguinal masses. Surgical excision is the appropriate treatment. We are presenting a case of a 47-year-old female patient who was admitted to the hospital with a left inguinal mass. Our patient underwent surgery, and a leiomyoma of the round ligament was found.